Developing A Pop-Up Storybook Based on Multicultural Education for Early Childhood Students - Khairunisa Kusumaningrum; Sugeng Bayu Wahyono (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2020)
This development research was aimed to produce multicultural education-based Pop-Up storybooks for early childhood students. This development research referred to the development design procedures developed by Thiagarajan et al. The development design was grouped into four development procedures, which include: (a) define, (b) design, (c) develop, and (d) disseminate. The product trial was carried out through 2 stages: the limited trial done with only 6 students of Grade B in TK Vanda Perta Rini Kalasan and the main trial done with 22 students of Grade B in TK Vanda Perta Rini Kalasan. The results of the product feasibility assessment score through product validation from media expert were 3.8 (very feasible) and from material expert were 4 (very feasible). Based on the result, it can be concluded that the pop-up book is effective to be used for introducing the understanding of multicultural education for early childhood students.